Applied sport management skills - Lussier, Robert N.; Kimball, David Charles 1959-
"Undergraduate-level text that provides students with a thorough understanding of the management principles used in sport organizations while also helping students developing their practical skills. The text is organized around the central management functions of planning, organizing, leading, and controlling"--Provided by publisher.